2022
DOI: 10.3390/rs14153652
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Calculating Water Quality Parameters by Integrating Space–Ground Hyperspectral Data and Spectral-In Situ Assay Data

Abstract: The effective integration of aerial remote sensing data and ground multi-source data has always been one of the difficulties of quantitative remote sensing. A new monitoring mode is designed, which installs the hyperspectral imager on the UAV and places a buoy spectrometer on the river. Water samples are collected simultaneously to obtain in situ assay data of total phosphorus, total nitrogen, COD, turbidity, and chlorophyll during data collection. The cross-correlogram spectral matching (CCSM) algorithm is us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…The high accuracy, precision, recall, and F1-score achieved by the CatBoost model highlight its effectiveness in classifying individuals into their respective obesity level categories. These findings are consistent with previous studies that have shown the advantages of gradient boosting algorithms, particularly CatBoost, in various classification tasks [36,37].…”
Section: Discussionsupporting
confidence: 93%
“…The high accuracy, precision, recall, and F1-score achieved by the CatBoost model highlight its effectiveness in classifying individuals into their respective obesity level categories. These findings are consistent with previous studies that have shown the advantages of gradient boosting algorithms, particularly CatBoost, in various classification tasks [36,37].…”
Section: Discussionsupporting
confidence: 93%
“…Root means square error (RMSE) represents the degree of dispersion of the model prediction results compared with the true value of the dependent variable, reflecting the stability of the model prediction performance [51]. The lower the value, the better the stability of the model prediction results.…”
Section: Accuracy Evaluationmentioning
confidence: 99%
“…These limitations make it challenging to obtain real-time data and monitor water quality on a large scale. As a result, alternative methods, such as remote sensing and machine learning algorithms, have gained popularity for their ability to overcome these constraints and provide more efficient and effective water quality monitoring solutions [131][132][133][134][135]. These methods can enable the collection and analysis of data from large water bodies, and can provide a more comprehensive understanding of water quality conditions at a higher spatiotemporal resolution, at a lower cost, and with less labor intensity [131][132][133][134][135].…”
Section: Satellite Applications For Water Resources and Quality Monit...mentioning
confidence: 99%